Qualitative research and literature review support the integrated Alzheimer's Disease Rating Scale (iADRS) content validity in early symptomatic AD - Delbecque, Laure; Elliott, Emma; Cleanthous, Sophie; Heinrich, Phoebe; Cano, Stefan; Wessels, Alette M.; Atkins, Alexandra S. (Journal of Prevention of Alzheimer's Disease, The, 2025)
The integrated Alzheimer's Disease Rating Scale (iADRS) is a measure of cognition and daily function used to evaluate treatment effects in Alzheimer's disease (AD) clinical trials. This study aimed to assess the content validity of the iADRS in early symptomatic AD, and to determine whether integrating assessment of cognition and function into a single measure of global disease severity is supported by the patients’ experience. A targeted literature review of qualitative research in AD and qualitative interviews with 25 care partners of individuals with early symptomatic AD were conducted. Interviews started with open-ended concept elicitation exploring the patient experience of AD from the care partner perspective, including how cognitive changes affect daily functioning. This was followed by cognitive debriefing of the ADCS-iADL items. Interview transcripts were analyzed thematically. Concepts extracted from the literature review and interviews were categorized into a conceptual model of patient experience of AD. A concept-to-item mapping exercise was conducted to assess the conceptual coverage of the iADRS. The literature review comprised sixty articles. Interviews were conducted with care partners of 7 individuals with Mild Cognitive Impairment (MCI)-AD and care partners of 18 individuals with dementia due to AD. The resulting conceptual model incorporated 75 concepts related to AD experience categorized into three overarching domains: Cognition, Daily Function and Other Symptoms/Impacts. Interview findings endorsed the close link between cognition and daily function. Concept-to-item mapping demonstrated all Cognition and Daily function sub-domains within the model were assessed by at least one iADRS item, except Work/Professional, providing supportive evidence that the iADRS covers concepts that reflect the patient experience of early symptomatic AD. This study offers a comprehensive conceptualisation of the patient experience of early symptomatic AD and highlights the intrinsic connection between cognition and daily function. The findings endorse the relevance of an integrated assessment of cognition and function and provide strong evidence for the content validity of the iADRS, highlighting its utility as a meaningful clinical outcome assessment (COA) for use as an endpoint in AD.